2011
DOI: 10.1051/0004-6361/201116561
|View full text |Cite
|
Sign up to set email alerts
|

A survey for near-infrared H2emission in Herbig Ae/Be stars: emission from the outer disks of HD 97048 and HD 100546

Abstract: We report on a sensitive search for H 2 1-0 S(1), 1-0 S(0) and 2-1 S(1) ro-vibrational emission at 2.12, 2.22 and 2.25 μm in a sample of 15 Herbig Ae/Be stars employing CRIRES, the ESO-VLT near-infrared high-resolution spectrograph, at R ∼ 90 000. We report the detection of the H 2 1-0 S(1) line toward HD 100546 and HD 97048. In the other 13 targets, the line is not detected. The H 2 1-0 S(0) and 2-1 S(1) lines are undetected in all sources. These observations are the first detection of near-IR H 2 emission in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 67 publications
(120 reference statements)
1
53
0
Order By: Relevance
“…The lack of emission closer to the star was taken as a possible sign of photo-dissociation of CO as [OI], and hence gas, seems to exist also in the inner 10 AU. Interestingly, Carmona et al (2011) found that the H 2 1-0 S(1) ro-vibrational line at 2.12 μm was not only clearly detected but extended from ∼5-10 AU out to >200 AU. Photo-dissociation in the inner disk regions and heating by high-energy UV and X-ray photons was suggested as a possible origin for the observed emission.…”
Section: Hd 97048 Resolved In Pah Continuum and Gas Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of emission closer to the star was taken as a possible sign of photo-dissociation of CO as [OI], and hence gas, seems to exist also in the inner 10 AU. Interestingly, Carmona et al (2011) found that the H 2 1-0 S(1) ro-vibrational line at 2.12 μm was not only clearly detected but extended from ∼5-10 AU out to >200 AU. Photo-dissociation in the inner disk regions and heating by high-energy UV and X-ray photons was suggested as a possible origin for the observed emission.…”
Section: Hd 97048 Resolved In Pah Continuum and Gas Emissionmentioning
confidence: 99%
“…Single-dish observations of the mm continuum emission suggest a circumstellar mass of ∼0.2 M (Henning et al 1998) but part of this mass is probably residing in an envelope, also seen in extended MIR emission (Prusti et al 1994;Siebenmorgen et al 2000), surrounding the star-disk system. Several gas emission lines ([OI], CO and H 2 ) have been detected and were, at least partly, spectrally and spatially resolved (Acke & van den Ancker 2006;van der Plas et al 2009;Martin-Zaïdi et al 2007Carmona et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly these are the only two Herbig AeBe sources where ro-vibrational H 2 emission has been detected so far (Carmona et al 2011). The velocity profile of the line suggests extended H 2 emission to more that 50 AU (radius) from the star (Carmona et al 2011).…”
Section: Disk Chemistry and Molecular Excitationmentioning
confidence: 99%
“…The associated magnetic fields would have A&A 564, A11 (2014) strong consequences for the formation and migration of planets (Fromang et al 2005;Bai & Stone 2013). The H 2 emission from warm (T = 1000-3000 K) gas was recently detected within 100 AU of more evolved T Tauri stars (TTSs) and Herbig Ae/Be stars, both in the near-infrared and far-ultraviolet (FUV) domains (e.g., Valenti et al 2000;Ardila et al 2002;Bary et al 2003;Carmona et al 2011). When studied at high spectral resolution, these lines split into two populations: most show narrow profiles centered on the stellar velocity, suggesting an origin in a warm disc atmosphere (quiescent H 2 ), but 30% of them display profiles blueshifted by 10-30 km s −1 , sometimes with blue wings extending up to -100 km s −1 , suggesting formation in an outflow (Takami et al 2004;Herczeg et al 2006;Greene et al 2010;Carmona et al 2011;France et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The H 2 emission from warm (T = 1000-3000 K) gas was recently detected within 100 AU of more evolved T Tauri stars (TTSs) and Herbig Ae/Be stars, both in the near-infrared and far-ultraviolet (FUV) domains (e.g., Valenti et al 2000;Ardila et al 2002;Bary et al 2003;Carmona et al 2011). When studied at high spectral resolution, these lines split into two populations: most show narrow profiles centered on the stellar velocity, suggesting an origin in a warm disc atmosphere (quiescent H 2 ), but 30% of them display profiles blueshifted by 10-30 km s −1 , sometimes with blue wings extending up to -100 km s −1 , suggesting formation in an outflow (Takami et al 2004;Herczeg et al 2006;Greene et al 2010;Carmona et al 2011;France et al 2012). In particular, long-slit spectra of DG Tau provide evidence of a warm H 2 outflow at -20 km s −1 , shifted by 30 AU along the blue jet direction and with an estimated width 80 AU (Takami et al 2004;Schneider et al 2013b).…”
Section: Introductionmentioning
confidence: 99%